2010
DOI: 10.1128/jb.01378-09
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Azole Antibiotics to Staphylococcus aureus Flavohemoglobin Increases Intracellular Oxidative Stress

Abstract: In this work, we report that flavohemoglobin contributes to the azole susceptibility of Staphylococcus aureus. We first observed that deletion of the flavohemoglobin gene leads to an increase in the viability of imidazoletreated S. aureus cells and that reversion to the wild-type phenotype occurs upon expression of flavohemoglobin from a multicopy plasmid. Further spectroscopic analyses showed that miconazole, the most efficient azole antibiotic against S. aureus, ligates to heme of both oxidized and reduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Furthermore, the fact that miconazole did not increase the DETA/NO-induced growth inhibition in an hmp -mutant strain, support that inhibition of flavohemoglobin [14] contributes to the antibacterial effect of miconazole in our experiments. Thus, the prolonged growth inhibition evoked by DETA/NO and miconazole in combination may be a result of interactions of miconazole with flavohemoglobin, causing both inhibition of NO dioxygenase activity and oxidative stress following high levels of cytotoxic superoxide production [14,15]. In agreement with our results, intracellular survival studies in activated NO-producing macrophages demonstrated decreased survival of miconazole-treated S. aureus compared to untreated bacteria [15].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the fact that miconazole did not increase the DETA/NO-induced growth inhibition in an hmp -mutant strain, support that inhibition of flavohemoglobin [14] contributes to the antibacterial effect of miconazole in our experiments. Thus, the prolonged growth inhibition evoked by DETA/NO and miconazole in combination may be a result of interactions of miconazole with flavohemoglobin, causing both inhibition of NO dioxygenase activity and oxidative stress following high levels of cytotoxic superoxide production [14,15]. In agreement with our results, intracellular survival studies in activated NO-producing macrophages demonstrated decreased survival of miconazole-treated S. aureus compared to untreated bacteria [15].…”
Section: Discussionsupporting
confidence: 84%
“…An explanation for the antibacterial activity of econazole against E. coli and S. aureus was already provided before. In these studies econazole was described as an inhibitor of flavohemoglobin . Further possible target systems of azole antifungals within Mtb metabolism have also been described .…”
Section: Discussionmentioning
confidence: 99%
“…This does not apply directly to bacteria; however, Mycobacterium smegmatis, another bacterium that is susceptible to miconazole, has been shown to contain a cytochrome P450 monooxygenase that is orthologous to 14α‐sterol demethylase and strongly binds miconazole 12 . Direct membrane damage has also been suggested as a mechanism of action in staphylococci, 6 and it is has recently been reported that miconazole induces intracellular reactive oxygen species in S. aureus 13 . As a clear mechanism is not understood (and multiple mechanisms may be present), it is difficult to hypothesize possible explanations for the impact of species or meticillin resistance on miconazole susceptibility.…”
Section: Discussionmentioning
confidence: 99%